A Comprehensive Systematic Review of The Relationship between Smoking and The Risk of Tuberculosis Relapse after Treatment Completion - Dika Fahmi Khoirunnas (International Medical Journal Corp. Ltd, 2026)
Introduction: Tuberculosis (TB) remains a major global health challenge, with recurrence after treatment completion posing significant obstacles to disease control. Smoking has been implicated as a potential risk factor for TB recurrence, yet the evidence requires systematic synthesis. This review aims to comprehensively evaluate the relationship between smoking and TB recurrence risk among patients who have completed anti-tuberculosis treatment. Methods: A systematic screening of studies was conducted based on predefined eligibility criteria. Included studies examined patients with confirmed TB diagnosis and treatment completion, clearly defined smoking exposure, TB recurrence as an outcome, observational study designs or systematic reviews, minimum six months post-treatment follow-up, and rigorous methodology. Data extraction encompassed study characteristics, population details, smoking exposure assessment, recurrence definitions, outcome measures, effect estimates, and confounder adjustment strategies. Results: One hundred forty-six studies were included, predominantly conducted in Indonesia and other Asian countries. Sample sizes ranged from 5 to over 5,000 participants, with most studies involving adult pulmonary TB patients (mean age 58.5 years; male predominance 53.8-81.8%). Smoking was consistently associated with significantly increased TB recurrence risk. Darakhshan Ahmad et al. (2016) reported an odds ratio of 2.35 (95% CI: 1.48-3.74) for continued smoking post-treatment, increasing to 3.67 (95% CI: 1.55-8.71) for smoking exceeding ten years. N. Karminiasih et al. (2016) demonstrated an adjusted odds ratio of 3.6 (95% CI: 1.41-9.16) for smoking or smoke exposure during treatment. A dose-response relationship was evident, with greater intensity (>10 cigarettes/day) and longer duration conferring elevated risk. Several studies controlled for confounders including diabetes, HIV, nutritional status, and socioeconomic factors. Discussion: The synthesized evidence demonstrates a consistent, robust positive association between smoking and TB recurrence post-treatment. Biological plausibility is supported by mechanisms including impaired mucociliary clearance, alveolar macrophage dysfunction, reduced interferon-gamma production, and structural lung damage. However, significant heterogeneity exists in study designs, smoking definitions, recurrence ascertainment, and follow-up durations. Many studies lack distinction between true relapse and exogenous reinfection. Limited data on smoking cessation timing represents a critical evidence gap. Conclusion: Smoking constitutes a significant, modifiable risk factor for tuberculosis recurrence after treatment completion. The consistent dose-response relationship and biological plausibility strongly suggest causality. Comprehensive TB control programs must integrate smoking cessation interventions as an essential component of standard patient management. Future prospective cohort studies with standardized methodologies, molecular genotyping to distinguish relapse from reinfection, and rigorous evaluation of cessation interventions are urgently required.